Impact of oral administration of single strain Lactococcus lactis spp. cremoris on immune responses to keyhole limpet hemocyanin immunization and gut microbiota: A randomized placebo-controlled trial in healthy volunteers - Saghari, Mahdi; Gal, Pim; Grievink, Hendrika W.; Klaassen, Erica S.; Itano, Andrea; McHale, Duncan; Moerland, Matthijs (Frontiers in Immunology, 2022)
Lactococcus lactis spp. cremoris has been associated with promising immunomodulatory results in preclinical trials. The aim of this study was to investigate pharmacodynamic (PD) effects of three monoclonal microbial formulations of Lactococcus lactis spp. cremoris (EDP1066) on the immune response to keyhole limpet hemocyanin (KLH). Potential effects on the gut microbiota were also investigated. The trial was registered on Netherlands Trial Register (trial ID NL7519, https://trialsearch.who.int). Eighty-one healthy subjects (median 28, range 18-59 years) were randomized to 28 days of either enteric-coated capsules at five doses (n=13) (1.5*1012 total cells daily), freeze-dried powder at one dose (n=12) (3.0*1011 total cells daily) or five doses (n=12), or minitablets at one dose (n=12) or five doses (n=12), or placebo (n=20) prior to KLH immunization. Antibody responses and circulating regulatory T cells (Tregs) were measured after KLH immunization and skin responses were evaluated after a KLH rechallenge by Laser Speckle Contrast Imaging and multispectral imaging. Ex vivo lymphocyte (phytohemagglutinin) and monocyte (lipopolysaccharide) cytokine release assays were explored in minitablet treated groups only. The prevalence of Lactococcus lactis spp. cremoris in the gastrointestinal tract and the impact on the fecal microbiota were assessed by qPCR and 16S RNA sequencing, respectively. Repeated measures analysis of covariances revealed no significant treatment effects on the antibody responses to KLH, number of Tregs, or KLH skin rechallenge outcomes. Ex vivo lipopolysaccharide-driven cytokine responses in whole blood were lower in the low dose minitablet group compared to placebo: tumor necrosis factor (estimated difference (ED) from placebo): -44.2%, 95% confidence interval (CI) -65.3% - -10.3%), interleukin (IL)-1β (ED: -41.4%, 95% CI -63.5% - -5.8%), and IL-6 (ED: -39.2%, 95% CI -56.8% - -14.5%). The fecal presence of Lactococcus lactis spp. cremoris increased during treatment by all EDP1066 formulations and normalized 5 days post last dose. Microbiome α-diversity did not change by the treatments compared to placebo. The EDP1066 formulas did not affect the immune response to KLH immunization in healthy individuals. However, exposure to Lactococcus lactis spp. cremoris in minitablet formulation impacted ex vivo whole blood LPS cytokine response. The clinical impact of these effects awaits further investigations.